Design of a decision support system for making informed decisions about selection of machines for manufacturing leather garments - Zakharkevich, Oksana; Koshevko, Julia; Zhylenko, Tetyana; Shvets, Galina; Kuleshova, Svitlana; Onofriichuk, Volodymyr; Diakova, Alona (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates the process of selecting sewing machines for the manufacturing of products from artificial leather. Despite the active development of technological solutions for automation, the task of choosing optimal equipment remains relevant, requiring additional tools that can provide a connection between scientific approaches and industrial conditions. This paper reports the results of designing an automated decision support system for the selection of sewing equipment, aimed at bridging the gap between theoretical models and production needs. The technological advancement is based on a three-level database structure. At the data storage level, a matrix-based database of equipment parameters was constructed, ensuring the consistency of information regarding technological operations, materials, and machine characteristics. At the logical level, a multifactor analysis algorithm was developed, utilizing the principles of graph theory, a binary matrix, and the linear programming method to select the optimal equipment model. The representation level is an interactive interface based on MS Excel (USA). Input parameters are selected by simply clicking on buttons with corresponding names (seam type, worker qualification, material properties, and thickness). The system automatically analyzes the database and generates a list of recommended equipment in a table format. Verification was carried out through a survey involving 30 participants (86.7% were representatives of the academic community). The results show that 93.3% of respondents noted the high speed of the simulator while 90.0% rated its practicality and 86.7% its convenience. At the same time, certain shortcomings were identified, outlining areas for further research: 23.3% of those surveyed highlighted the need to expand the database, and 16.7% emphasized the necessity of implementing a Ukrainian-language version. It was established that the designed system is a universal tool that combines educational and practical-production dimensions. Its implementation in the educational process will contribute to achieving a number of program learning outcomes